Relationship between Mother's Knowledge of Basic Immunization and Completeness of Basic Immunization in Infants - Idawati, Idawati; Rosdiana; mulyani, Syarifah; Subhiah; Zahara, Juni (Trigin Institute, 2023)
Immunization is an effort to prevent health problems in infants. The government obliges five types of complete basic immunization which can be obtained free of charge. This study aims to determine the relationship between mother's knowledge of basic immunization and the completeness of basic immunization in infants. This step is so that children get immunity individually. At least 70% of the population in an area must be immunized. The first step, the researcher collects 20 research journals that are relevant to the topics discussed and published in the last 10 years. In the second step, the researcher began to identify the characteristics of each research journal. The results of the identification process will be displayed in a tabular form. in the next step, the researcher will analyze and look for points of similarity (resemblance) and difference (difference) from the research results of each journal and describe them in paragraph form. In the next step, researchers criticize and compare it with the research results of each journal. In the final step, the researcher summarizes the results obtained from the analysis process that has been carried out. The results of the study explain that there are eighteen variables studied. The order of these variables is based on the highest frequency, namely: mother knowledge; mother's education level; mother's manner; Family support; mother's occupation; mother's age; officer service; service distance; Mother's trust; Gender; nutritional status; Way of birth; birthweight; Order of birth; number of children; officer roles; Socio-economic; and Marital status